KEBIJAKAN SINGLE SALARY DALAM UNDANG-UNDANG TENTANG APARATUR SIPIL NEGARA YANG BERPIJAK PADA KEADILAN DAN KELAYAKAN - Mohammad Iqbal Asshidiqii; Puti Priyana (Paulus Law Journal, 2023)
Various problems and dynamics regarding personnel law in Indonesia are now increasingly demanding a policy that provides more welfare with a decent and fair payroll system. Encouraged by changes in the legal regulation in the field of Civil Service, where the Law on State Civil Apparatus requires a change in the payroll system for civil servants. Tukin, which is owned by the Ministry of Finance as the highest in Indonesia, has led to corruption, meaning that it does not provide guarantees that the large Tukin is able to keep employees away from actions that are contrary to the law. This research uses juridical research methods with literature studies of primary and secondary legal materials and also a regulatory approach, analytical approach, as well as a conceptual approach to be a research method in this research. Given the position of ASN as such a very important part in the wheels of Government. Through the Law on State Civil Apparatus, ASN (PNS and P3K) get their rights, obligations, and responsibilities as Government officials who provide public services to the community. The amount of allowance given to employees shows that in reality, the granting of civil servants' tukin has not been based on the actual performance measures of employees. The measures used are more based on highly immeasurable values and behaviors. The concept of a single salary system as a system that can be considered impartial and able to provide equitable and decent welfare for employees.